1964
DOI: 10.1084/jem.120.6.1087
|View full text |Cite
|
Sign up to set email alerts
|

Further Observations on the Relevance of Serologic Recapitulations of Human Infection With Influenza Viruses

Abstract: The results of studies on the age distribution of antibodies, on the range of antibody response to monovalent vaccines by age, and on the age-specific characteristics of antibody demonstrated by serum adsorption tests, have indicated that periods of past prevalence of strains closely related antigenicalIy to swine and Asian strains can be identified. Thus a swine-like virus is thought to have been involved in the pandemic of 1918 and an Asian-fike one in the pandemic of 1889-90.A basic tenet of these serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

1965
1965
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
2
22
0
1
Order By: Relevance
“…In both cases, rather than evolving directly from its predecessor via antigenic drift, a new lineage with distinct antigenic properties evidently arose via the acquisition of an "old" and rare homosubtypic H1 HA variant by intrasubtype reassortment. The replacement of the pandemic HA by a heterologous H1 HA offers a simple resolution to the long-standing conundrum that antibodies to the swine/pandemic virus HA suddenly disappeared in those born after ∼1922 (16,17,20,30,31), even though seasonal H1N1 obviously continued to circulate (SI Appendix, SI Text). However, less parsimonious scenarios, such as a separate cross-species introduction of the seasonal H1 HA from birds or even from other mammalian hosts such as horses, in or shortly after 1918, cannot be formally excluded (SI Appendix, SI Text and Fig.…”
Section: Significancementioning
confidence: 99%
“…In both cases, rather than evolving directly from its predecessor via antigenic drift, a new lineage with distinct antigenic properties evidently arose via the acquisition of an "old" and rare homosubtypic H1 HA variant by intrasubtype reassortment. The replacement of the pandemic HA by a heterologous H1 HA offers a simple resolution to the long-standing conundrum that antibodies to the swine/pandemic virus HA suddenly disappeared in those born after ∼1922 (16,17,20,30,31), even though seasonal H1N1 obviously continued to circulate (SI Appendix, SI Text). However, less parsimonious scenarios, such as a separate cross-species introduction of the seasonal H1 HA from birds or even from other mammalian hosts such as horses, in or shortly after 1918, cannot be formally excluded (SI Appendix, SI Text and Fig.…”
Section: Significancementioning
confidence: 99%
“…proportion of sera from young and older adults but not from children led him to argue that this virus or one of similar antigenic composition had been widely prevalent in the recent past. He agreed therefore with Davenport et al (1964) has shown that the swine virus antibody in adults over 40 years of age is specific in its reaction, whereas that from younger persons has the character of cross-reacting antibody. The finding of a shift in age distribution of swine virus antibodies between 1935 and 1953 both in the U.S.A. and in Britain Davenport et at.…”
Section: Resultsmentioning
confidence: 56%
“…There is no epidemiological evidence suggesting that equine influenza is a disease at all related to human infection and the serological findings therefore remain unexplained. Davenport et al (1964) use the term 'serological archaeology' for the type of work which led to this discovery and doubtless there is much more yet to be discovered about the viruses of former human influenza epidemics if the appropriate antigens could be located. Certainly it would be unwise to speculate concerning the exact time-relationships between past virus infections and epidemics.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of virus with heterologous antibodies cannot be described in terms of the isotherm established for the reaction of virus with homologous antibodies, so to test whether or not the reaction of virus with a given antiserum follows the isotherm established for the strain of virus employed makes it possible to discriminate objectively the reactions of virus with homologous and heterologous antibody (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been utiIized in order to test the specificity of antibody patterns recorded by conventional hemagglutination inhibition (HI) tests in human sera (2,4,5) and to analyse the antigenic composition of hemagglutinins obtained by ether-treatment of influenza virus strains (3,8,9,10).…”
Section: Introductionmentioning
confidence: 99%